Optimal Chest Compression Rate and Compression to Ventilation Ratio in Delivery Room Resuscitation: Evidence from Newborn Piglets and Neonatal Manikins - Solevåg, Anne Lee; Schmölzer, Georg M. (Frontiers in Pediatrics, 2017)
Cardiopulmonary resuscitation (CPR) duration until return of spontaneous circulation (ROSC) influences survival and neurologic outcomes after delivery room CPR. High quality chest compressions (CC) improve cerebral and myocardial perfusion. Improved myocardial perfusion increases the likelihood of a faster ROSC. Thus optimizing CC quality may improve outcomes both by preserving cerebral blood flow during CPR, and by reducing the recovery time. CC quality is determined by rate, CC to ventilation (C:V) ratio, and applied force, which are influenced by the CC provider. Thus, provider performance should be taken into account. Neonatal resuscitation guidelines recommend a 3:1 C:V ratio. CCs should be delivered at a rate of 90/min synchronized with ventilations at a rate of 30/min to achieve a total of 120 events/min. Despite a lack of scientific evidence supporting this, the investigation of alternative CC interventions in human neonates is ethically challenging. Also, the infrequent occurrence of extensive CPR measures in the delivery room make randomized controlled trials difficult to perform. Thus, many biomechanical aspects of CC have been investigated in animal and manikin models. Despite mathematical and physiological rationales that higher rates and uninterrupted CC improve CPR hemodynamics, studies indicate that provider fatigue is more pronounced when CC are performed continuously compared to when a pause is inserted after every 3rd CC as currently recommended. A higher rate (e.g.120/min) is also more fatiguing, which affects CC quality. In post-transitional piglets with asphyxia-induced cardiac arrest, there was no benefit of performing continuous CC at a rate of 90/min. Not only rate, but duty cycle, i.e. the duration of CC/total cycle time, is a known determinant of CC effectiveness. However, duty cycle cannot be controlled with manual CC. Mechanical/automated CC in neonatal CPR has not been explored, and feedback systems are under-investigated in this population. Evidence indicates that providers perform CC at rates both higher and lower than recommended. Video recording of delivery room CRP has been increasingly applied and observational studies of what is actually done in relation to outcomes could be useful. Different CC rates and ratios should also be investigated under controlled experimental conditions in animals during perinatal transition.